(untitled) (TAMADDUN NURI JURNALI, 2024)
In this article, the impact of S. Ahmed’s "Horizon" trilogy, one of the brightest representatives of Uzbek literature, on our language, and its contribution to the development of our literature is analyzed. The article has an analytical character, in which the author provides general information about the trilogy. gives information, analyzes, justifies each of his views.